2012
DOI: 10.1111/j.1473-2165.2011.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Topically applied l‐carnitine effectively reduces sebum secretion in human skin

Abstract: Our results show that the treatment of human sebocytes with L-carnitine significantly augments β-oxidation and significantly decreases intracellular lipid content in human sebocytes. Topically applied L-carnitine is bioavailable and leads to a significant sebum reduction in vivo. In conclusion, L-carnitine represents a valuable compound, produced naturally within the body, for the topical treatment of oily skin in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…The study by Peirano et al showed that Lcarnitine significantly augmented β-oxidation and significantly decreased intracellular lipid content in human sebocytes (9). Topical application of L-carnitine for 3 weeks significantly reduced the sebum secretion rate compared to the treatment with placebo (9).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The study by Peirano et al showed that Lcarnitine significantly augmented β-oxidation and significantly decreased intracellular lipid content in human sebocytes (9). Topical application of L-carnitine for 3 weeks significantly reduced the sebum secretion rate compared to the treatment with placebo (9).…”
Section: Discussionmentioning
confidence: 96%
“…In Germany, the moisturizer, containing licochalcone A, L-carnitine and 1,2decanediol, has been proved to improve disease severity in patients with mild to moderate severe acne (8,9). Greater reduction in the total lesion counts, papules and pustules, P. acnes colonization and sebum production were found at week 8 of treatment in the active formulation group compared to baseline.…”
Section: Introductionmentioning
confidence: 92%
“…The anti‐sebum efficacy of the guava toner was higher than the consumers’ satisfied level (10%) . Sebum secretion was greater suppressed by the presenting toners than that was reported in 2% L ‐carnitine product (0.71 ± 0.96 following 3 week application) . Furthermore, the guava toner was noted to be superior in anti‐sebum efficacy in male than female volunteers as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed the effect of topically applied L-carnitine for reducing sebum secretion. 18 Draelos and colleagues conducted a randomized, double-blind, clinical trial evaluating the effect of 2% niacinamide on facial sebum production. They concluded that 2% niacinamide might aid in an improved cosmetic appearance for facial shine reduction, but further studies are necessary to characterize the mechanism of action.…”
Section: Reducing Sebum Secretionmentioning
confidence: 98%